Protective and therapeutic effects of hesperidin in an experimental colitis model - Serdal Öğüt; Esra Güzel; Serdar Aktaş (International Journal of Secondary Metabolite)
Ulcerative colitis is a gastrointestinal problem with increasing prevalence. In this study, the effect of hesperidin (commonly found in citrus white peel) on colitis was investigated. For this purpose, 28 Wistar albino female rats, 3–4 months old and weighing between 250–350 g, were used in the study. Rats were randomly divided into four groups: control (n=7), colitis (n=7), protective effect (n=7), and treatment (n=7) groups. Colitis was induced in rats with acetic acid (except control), and hesperidin was then administered at 150 mg/kg for 1 week before and after colitis. At the end of the study, IFN-γ and IL-6 values in blood, TAS, TOS, and OSI in tissue were evaluated. Intestinal tissues were assessed visually by haematoxylin and eosin staining. Our results showed that the levels of IFN-γ and IL-6 were highest in the colitis group and lowest in the treatment group, with statistical significance. The most histopathological damage was seen in the colitis group, while less prevalent in the treatment and control groups. The results of the study show that hesperidin had limited protective and therapeutic effects on experimental colitis mouse models.